Pattern of Orbital Diseases at a Tertiary Oculoplastic Center: Doi: 10.36351/pjo.v37i1.1154 - idris, Mohammad; Yaqoob, Hassan; Khan, Muhammad Adnan; Zar, Adnan; Ullah, Saif (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the causes and frequency of orbital involvement by systemic disorders and non-ocular trauma at a tertiary Oculoplastic centre. Study Design: Descriptive cross-sectional retrospective study. Ophthalmology unit Place and Duration of Study: Department of Ophthalmology, Lady Reading Hospital Medical teaching Institute, Peshawar from January 2012 and Dec 2016. Methods: A total of 45 patients were included in this study. Patients’ demographics, clinical cause of orbitopathy and time delay between the problem noticed by the patient and presentation were recorded. Orbitopathy included the presence of corneal and conjunctival changes, optic nerve disorders, proptosis, orbital bone changes and soft tissue swelling of eyelids. The data was analyzed using SPSS software (version 22). The frequency (percentage) and mean ± standard deviation were reported for categorical variables. Results: Mean age of the patients was 28.89 ± 22.02 years. There were 26 (57.8%) males 19 (42.2%) females. Commonest disorder was Bacterial Infection in 16 (35.6%) patients followed by Thyroid orbitopathy, which was seen in 14 (31.1%) cases. Other causes included Leukemia, Lymphoma, Retrobulbar Hemorrhage, Neurofibromatosis, Neuroblastoma, Maxillary Osteosarcoma, Teratoma and Fungal Infection. Time delay between presentation of orbital swelling and first noticed by patient was 147.02 ± 155.18 weeks in male while in female the time delay was 148.79 ± 146.47 weeks. Conclusion: The commonest inflammation was due to thyroid, commonest infection was bacterial infection and commonest tumor was leukemia. Imaging and proper workup is important to properly treat any orbital disease. Key Words: Orbit, Ocular trauma, Neuroblastoma, Orbital lymphoma.